2009
DOI: 10.1097/aln.0b013e31819c45e5
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Pentax-AWS® in 293 Patients with Difficult Airways

Abstract: The success rate of tracheal intubation using the Pentax-AWS was high in patients with difficult laryngoscopy with a Macintosh laryngoscope and in patients with predicted difficult intubation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 173 publications
(137 citation statements)
references
References 19 publications
2
132
0
3
Order By: Relevance
“…Les donne´es suivantes ont e´te´mesure´es et enregistre´es : temps jusqu'a`intubation trache´ale re´ussie (crite`re d'e´valuation principal), taux de re´ussite global, temps jusqu'a`visualisation des cordes vocales, pourcentage d'ouverture glottique, compression dentaire et facilited 'intubation. Résultats Dans les cas de voies ae´riennes normales, les temps (moyenne [e´cart interquartile]) jusqu'a`intubation trache´ale e´taient plus courts avec le Pentax-AWS (12,1 [10,1-14,4] sec) et le GlideScope (14,3 [12,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]6] sec) qu'avec le laryngoscope Macintosh (16,5 [13,,1] sec) (P \ 0,03 pour les deux). La diffe´rence de temps entre les deux vide´olaryngoscopes n'e´tait pas significative d'un point de vue statistique.…”
Section: Résuméunclassified
“…Les donne´es suivantes ont e´te´mesure´es et enregistre´es : temps jusqu'a`intubation trache´ale re´ussie (crite`re d'e´valuation principal), taux de re´ussite global, temps jusqu'a`visualisation des cordes vocales, pourcentage d'ouverture glottique, compression dentaire et facilited 'intubation. Résultats Dans les cas de voies ae´riennes normales, les temps (moyenne [e´cart interquartile]) jusqu'a`intubation trache´ale e´taient plus courts avec le Pentax-AWS (12,1 [10,1-14,4] sec) et le GlideScope (14,3 [12,[4][5][6][7][8][9][10][11][12][13][14][15][16][17]6] sec) qu'avec le laryngoscope Macintosh (16,5 [13,,1] sec) (P \ 0,03 pour les deux). La diffe´rence de temps entre les deux vide´olaryngoscopes n'e´tait pas significative d'un point de vue statistique.…”
Section: Résuméunclassified
“…In addition, its routine use may be impractical, partly because of the high cost of purchasing and maintaining the device. Rigid indirect-optical laryngoscopes (or 'videolaryngoscopes'), which are known to be useful for orotracheal intubation [7][8][9], may well be useful for nasotracheal intubation. Ono and colleagues, in this issue of the Journal of Anesthesia [2], studied 103 patients (without limited mouth opening), to assess the efficacy of the Airway Scope, and nasotracheal intubation was always successful within 30 s. A previous study [10] has also reported that nasotracheal intubation using another videolaryngoscope (Glidescope) was always successful in 34 patients.…”
Section: Methods Of Nasotracheal Intubationmentioning
confidence: 99%
“…When compared to the conventional Macintosh laryngoscope, the AWS has been proved to be an effective intubation device not only for patients with normal airways [2], but also for cases with difficult airways [3].…”
Section: Table No Figuresmentioning
confidence: 99%